EVALUATION OF GLYCOSYLATED HEMOGLOBIN AND ELECTROLYTE STATUS IN DIABETIC KETOACIDOSIS - Julius, A; Praveen Kumar, J; Chidambaram, R; kumar, R Sri; Deepa, M (International Journal of Clinical and Biomedical Research, 2015)
Background: The present study was conducted to evaluate glycosylated hemoglobin and electrolyte status in Diabetic ketoacidosis subjects compared with controlled type II diabetes mellitus. Methods: Totally 100 subjects were included in this study (75 known DKA subjects and 25 controlled type II Diabetes Mellitus subjects). 5ml of venous blood samples are collected from subjects, Biochemical parameters performed Fasting blood sugar, Post prandial blood sugar by Glucose oxidase and peroxidase method, Glycosylated hemoglobin by Ion exchange High performance liquid chromatography, serum electrolytes levels are estimated by Ion selective electrode method. Results: The serum levels of FBS, PPBS, HbA1c levels are high in DKA compared with controlled Type II DM. the serum levels of sodium are significantly decreased in DKA compared with controlled Type II DM. The serum levels of potassium and chloride are high in DKA compared with controlled Type II DM. Conclusion: We concluded that electrolyte imbalance is high in DKA due to hyperglycemic hyper-osmolality and insulin deficiency frequently leads to electrolyte imbalance. HbA1c, FBS, PPBS levels are elevated in DKA due to uncontrolled hyperglycemia. KEYWORDS: Peroxidase method; Fasting blood sugar; HbA1c; Glycosylated hemoglobin.